Parasitic consideration for differential capacitive sensor - Nurul Arfah Che Mustapha; A. H. M. Zahirul Alam; Sheroz Khan; Amelia Wong Azman (Institute of Advanced Engineering and Science, 2019)
Parasitic integration for a single supply differential capacitive sensing technique is presented in this paper. In real capacitive sensor measurement, parasitic impedance exists in its measurement. This paper objective is to study the effect of capacitive and resistive parasitic to the capacitive sensor circuit. The differential capacitive sensor circuit derivation theory is elaborated first. Then, comparison is made using simulation. Test was carried out using frequency from 40 kHz up to 400 kHz. Result is presented and have shown good linearity of 0.99984 at 300 kHz, R-squared value. This capacitive sensor is expected to be used for energy harvesting application.